The primary unfolded protein response transducer endoplasmic reticulum-to-nucleus signaling 1 is downregulated in livers of human nonalcoholic steatohepatitis patients - El Hussain Shamsa; Kezhong Zhang (Wolters Kluwer Medknow Publications, 2018)
Background: The Unfolded Protein Response (UPR) is an elegant signaling pathway from the Endoplasmic Reticulum (ER) to protect cells from stress caused by accumulation of unfolded or misfolded proteins in the ER lumen. ER-to-Nucleus Signaling 1 (IRE1, also called ERN1), an ER-localized protein kinase and endoribonuclease (RNase), is the most conserved transducer of the UPR signaling pathway. In this study, we investigated expression levels of IRE1 in the livers of human non-alcoholic steatohepatitis (NASH) patients. Methods: We analyzed the expression profiles of the primary UPR transducer IRE1 in the livers of human NASH patients based on the microarray gene expression datasets obtained from public domain. Results: Our analyses indicated that expression levels of IRE1 were decreased in the livers of human obese patients with NASH, compared to those of obese patients without NASH. Conclusions: Our analysis result is consistent with the role of IRE1-mediated UPR in preserving cellular homeostasis and functions and in protecting organisms from injuries. This study provides important information in regard to the activation and functional involvement of the UPR signaling pathway in human NASH.